THU0180 Lack of Early Change in Disease Activity Score Predicts The Likelihood of Achieving Low Disease Activity at Month 6: Tofacitinib Monotherapy versus Methotrexate in Methotrexate-Naïve Patients with Rheumatoid Arthritis. (15th July 2016) - Keystone, E.; van Vollenhoven, R.F.; Wilkinson, B.; Fallon, L.; Hwang, L.-J.; Chapman, D.; DeMasi, R.; Lee, E.B.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). Treatment guidelines recommend targeting remission or low disease activity (LDA), herein defined as Disease Activity Scores ≤3.2 based on 28 joint counts (DAS28≤3.2) and adjusting therapy after 3–6 months 1 (Mos). Predicting the likelihood of clinical response may help inform early treatment decisions. Objectives: To understand the relationship between timing and magnitude of early changes in DAS28, erythrocyte sedimentation rate (DAS28-4[ESR]) and the likelihood of achieving LDA at Mo 6 in RA patients (pts) naïve to methotrexate (MTX). Methods: In a Phase 3 study (ORAL Start; NCT01039688 ), MTX-naïve RA pts were randomised 2:2:1 to the following monotherapies: tofacitinib 5 mg twice daily (BID), tofacitinib 10 mg BID or MTX. Conditional probability of pts achieving LDA at Mo 6 were calculated, given failure to achieve DAS28-4(ESR) improvement from baseline (range ≥0.3 to 1.8) at Mo 1 or 3. One-year data with non-responder imputation for missing values was used. Results: 948 pts received treatment; tofacitinib 5 mg BID (n=370), tofacitinib 10 mg BID (n=394) or MTX (n=184); results previously reported. 2 In this post-hoc analysis, of those patients who failed to achieve DAS28-4(ESR) improvement from baseline ≥1.2 at Mo 3, 6.8% for tofacitinib 5 mg BID, 11.3% for tofacitinib 10 mg BID and 6.2% for MTX achieved LDA at Mo 6 (Table ). A minority of pts (74/353 [20.9%]) receiving tofacitinib 5 mg BID failed to achieve DAS28-4(ESR) improvement ≥1.2 from baseline at Mo 3, while a greater proportion failed for MTX (65/171 [38.0%]). Failure to achieve DAS28-4(ESR) improvement from baseline at Mo 3 (range ≥0.30–1.8) for tofacitinib 5 mg BID and MTX was associated with a low probability (≤10%) of achieving LDA at Mo 6. For tofacitinib 5 mg BID, failure to achieve lower thresholds of DAS28-4(ESR) improvement (range ≥0.3 to 0.9) at Mo 1 was associated with lower probability of LDA at Mo 6 than higher DAS28-4(ESR) thresholds (≥1.2–1.8) (Table ). Conclusions: Failure to achieve DAS28-4(ESR) improvement ≥1.2 from baseline at Mo 3 was associated with a low probability of achieving LDA at Mo 6 (≤6.8%) for tofacitinib 5 mg BID and MTX. For the minority of MTX-naïve RA pts treated with tofacitinib 5 mg BID or MTX who failed to achieve a minimal clinical response (DAS28-4[ESR] improvement ≥1.2) by Mo 3, another treatment option can be considered at Mo 3, as there is a low probability of reaching LDA at Mo 6. References: Smolen J et al. Ann Rheum Dis 2016;75(1):3–15. Lee EB et al. N Engl J Med 2014;370:2377–2386. Acknowledgement: This study was sponsored by Pfizer Inc. Editorial support was provided by Rebecca Bright, PhD, of Complete Medical Communications, and funded by Pfizer Inc. Disclosure of Interest: E. Keystone Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, R. F. van Vollenhoven Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, B. Wilkinson Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Fallon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L.-J. Hwang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Chapman Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. DeMasi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. B. Lee Consultant for: Pfizer Inc